2017
DOI: 10.1055/s-0036-1588438
|View full text |Cite
|
Sign up to set email alerts
|

C4 Pictet–Spengler Reactions for the Synthesis of Core Structures in Hyrtiazepine Alkaloids

Abstract: The hyrtiazepine alkaloids are a family of bisindole natural products that have the azepinoindole backbone. We developed a biomimetic approach by constructing the azepinoindole core in a one-pot manner through 1,4-diazabicyclo[2.2.2]octane/2,2,2-trifluoroethanol (DABCO/TFE) promoted Pictet–Spengler reaction onto the C-4 position of tryptophan. This strategy allowed the synthesis of common key structures of these families. The key intermediate can be converted into the 3H-pyrano[2,3-b:5,6-e′]diindol intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, because of the nucleophilicity of indole at C2 and C3, numerous variants of the Pictet–Spengler reaction lead to structurally related compounds, such as 1,2,3,4-tetrahydropyrazino­[1,2- a ]­indoles 2 , tetrahydro-γ-carbolines 3 , and 1,3,4,5-tetrahydropyrrolo­[4,3,2- de ]­isoquinolines 4 , (Figure ). These so-called iso-Pictet–Spengler reactions are far less studied than the venerable historical reaction, despite allowing access to interesting heterocycles …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, because of the nucleophilicity of indole at C2 and C3, numerous variants of the Pictet–Spengler reaction lead to structurally related compounds, such as 1,2,3,4-tetrahydropyrazino­[1,2- a ]­indoles 2 , tetrahydro-γ-carbolines 3 , and 1,3,4,5-tetrahydropyrrolo­[4,3,2- de ]­isoquinolines 4 , (Figure ). These so-called iso-Pictet–Spengler reactions are far less studied than the venerable historical reaction, despite allowing access to interesting heterocycles …”
Section: Introductionmentioning
confidence: 99%
“…They can be roughly classified into two categories. One focuses on the functional group manipulations of 3,4-disubstituted indoles as the key strategy to form the tricyclic azepino­[5,4,3- cd ]­indole skeleton . The other generally involves the construction of this core structure starting from the indole ring formation .…”
Section: Introductionmentioning
confidence: 99%
“…In our continuing efforts in the indole chemistry, [31][32][33][34][35][36][37][38][39][40][41][42][43] we recently reported a concise formation of isochromeno [3,4-b]indolines from 2-benzyloxy-3-bromoindolines were achieved using a silver salt. 44) While extending the utility of the silver-mediated functionalization, we preliminary found that the protocol is also applicable for the synthesis of 2,3-dialkoxyinolines by using alcohol as a nucleophile, which could be converting to 3-alkoxyindoles through a selective elimination of the alkoxide at the C-2 position (Chart 2b).…”
mentioning
confidence: 99%